2022
DOI: 10.1111/cen.14813
|View full text |Cite
|
Sign up to set email alerts
|

The risk of chronic kidney disease development in adult patients with chronic hypoparathyroidism treated with rhPTH(1‐84): A retrospective cohort study

Abstract: Objective This study assessed the risk of developing chronic kidney disease (CKD) and decline in estimated glomerular filtration rate (eGFR) over a period of up to 5 years in adult patients with chronic hypoparathyroidism treated with recombinant human parathyroid hormone (1‐84) (rhPTH[1‐84]) compared with a historical control cohort of patients not treated with rhPTH(1‐84). Design Retrospective cohort study of patients with chronic hypoparathyroidism treated with rhPTH(1‐84) derived from the REPLACE (NCT00732… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“… 9 In a previous study, patients who received rhPTH(1–84) had a significantly lower risk of chronic kidney disease over a 5-yr period compared to a historical control cohort of patients with HypoPT who received conventional treatment. 36 …”
Section: Discussionmentioning
confidence: 99%
“… 9 In a previous study, patients who received rhPTH(1–84) had a significantly lower risk of chronic kidney disease over a 5-yr period compared to a historical control cohort of patients with HypoPT who received conventional treatment. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective cohort studies of adults with chronic hypoparathyroidism treated with PTH therapy as an adjunctive treatment to conventional therapy had preservation of eGFR over 5 years, in contrast to a decline in eGFR in historical control cohorts [13][14][15]. A retrospective cohort study by Rejnmark et al showed that participants with chronic hypoparathyroidism from randomized, double-blind, placebo-controlled trials and open-label studies treated with recombinant human (rh) PTH (1-84) had a 53% lower risk of developing CKD (HR 0.5, 95% CI 0.3-0.9) and 65% lower risk for sustained eGFR decline C 30% from baseline (HR 0.4, 95% CI 0.1-0.9) compared with a historical control cohort of adults with chronic hypoparathyroidism selected from an electronic medical record database who had a prescription for active vitamin D but no use of rhPTH (1-84) or teriparatide [15]. These findings suggest that, in contrast to conventional therapy, PTH therapy may have a protective effect on renal function in individuals with hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 99%